Telecommunication: Sector Working Paper - World Bank.; McNamara, Robert S. (Washington: World Bank, 1971)
This publication describes telecommunication as the central nervous systems of complex societies, transmitting information and commands between their various parts. Without these facilities, many dimensions of life in interrelated communities, especially government and economic activity, could not function efficiently, if at all.
ne 21/03/2018
Loan
Keywords: Telecommunication